DETERMINANTS AND EXTENT OF INCOME DIVERSIFICATION AMONG MILLET FARMING HOUSEHOLDS IN POTISKUM, YOBE STATE, NIGERIA - Bappa, A. A.; Bose, A. A.; Suleiman, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed income diversification on the livelihood of millet farmers in Potiskum Local Government Area of Yobe State, Nigeria. Stratified random sampling technique was used in selecting 335 farmers. Primary data were collected using structured questionnaires through Kobo collect and analyzed using descriptive statistics, Simpson Index of Diversification (SID), and logistic regression models. The findings revealed that, millet farming is dominated by middle-aged males with a mean age of 45 years and a mean household size of 11 persons. The average farm size was 2.72 hectares. The mean Simpson Index value was 0.5124. The results of the logistic regression showed that, access to credit (0.5181) and extension services (0.3878) significantly enhanced diversification at P<0.01, while exposure to climate shocks (-0.6048) significantly reduced diversification capacity at P<0.05. Also, rainfall sufficiency (0.3981) had a positive effect at P<0.05, and age (-0.0149) had a negative effect on income diversification. The study concludes that income diversification is a viable strategy for improving rural livelihoods and reducing poverty among millet farmers in the study area. The study recommended that strengthening access to credit and extension services, improving market infrastructure, promoting non-farm enterprise training, and encouraging youth participation in diversified livelihood activities in the study area.